The Internet and Computer User Profile: a questionnaire for determining intervention targets in occupational therapy at mental health vocational centers. - Regev, Sivan; Hadas-Lidor, Noami; Rosenberg, Limor (Disability & Rehabilitation: Assistive Technology, 2016)
Purpose: In this study, the assessment tool “Internet and Computer User Profile” questionnaire (ICUP) is presented and validated. It was developed in order to gather information for setting intervention goals to meet current demands.Methods: Sixty-eight subjects aged 23–68 participated in the study. The study group (n = 28) was sampled from two vocational centers. The control group consisted of 40 participants from the general population that were sampled by convenience sampling based on the demographics of the study group. Subjects from both groups answered the ICUP questionnaire. Subjects of the study group answered the General Self- Efficacy (GSE) questionnaire and performed the Assessment of Computer Task Performance (ACTP) test in order to examine the convergent validity of the ICUP. Twenty subjects from both groups retook the ICUP questionnaire in order to obtaintest-retestresults. Differences between groups were tested using multiple analysis of variance (MANOVA) tests. Pearson and Spearman's tests were used for calculating correlations. Cronbach's alpha coefficient andkequivalent were used to assess internal consistency.Results: The results indicate that the questionnaire is valid and reliable. They emphasize that the layout of the ICUP items facilitates in making a comprehensive examination of the client's perception regarding his participation in computer and internet activities.Implications for RehabiliationThe assessment tool “Internet and Computer User Profile” (ICUP) questionnaire is a novel assessment tool that evaluates operative use and individual perception of computer activities.The questionnaire is valid and reliable for use with participants of vocational centers dealing with mental illness.It is essential to facilitate access to computers for people with mental illnesses, seeing that they express similar interest in computers and internet as people from the general population of the same age.Early intervention will be particularly effective for young adults dealing with mental illness, since the digital gap between them and young people in general is relatively small.